A history of Southeast Asia critical crossroads - Reid, Anthony 1939- (John Wiley & Sons Inc., 2015)
"Incorporates environmental, social, economic, and gender issues to tell a multi-dimensional story of Southeast Asian history from earliest times to the present"--